Apport de l’information géospatiale dans les décisions d’aménagement du territoire - Hélène Rey-Valette; Pierre Maurel; Chady Jabbour; Camille Cousin; Sandra Luque; Olivier Billaud; Jean Michel Salles (Développement Durable et Territoires)
This paper aims to investigate the extent to which ecosystem services maps can improve land-use planning decisions by strengthening the consideration of environmental issues. The methodology used is based on an experimental workshop simulating a participatory decision-making process for planning choices by a panel of territorial actors. The protocol of the workshop consists in comparing the choices of location of new areas to be urbanized based firstly on a fine land cover map and secondly, by using a sample of ecosystem services maps. The results show the participants’ interest in having ecosystem service maps for planning decision making. According to them, they bring an added value in terms of discovery, coherence, efficiency and acceptability of multifunctional space management practices. However, the operational actors of territorial engineering still make very little use of these maps derived from remote sensing and participatory workshops.